Acceptability of correlated lecture series with a Modified Problem Based Learning Orientation among First Year Medical Students of Iloilo Doctor's College of Medicine - Dalisay, Pacifico Jr. S.
This research describes the acceptability of a correlated lecture series with a modified problem based orientation among first year medical students of the Iloilo Doctor's College of Medicine. By tradition, the medical profession has been taught in the traditional, lecture type, visual aid presentation with evaluation in the form of written sometimes oral examination. It has produced prominent medical practioners who have excelled in their respective chosen field of specialty. About two decades ago, this method of teaching has been questioned. Proponents of this teaching strategy claim that students develop a knowledge base characterized by breath, depth, and flexibility, and skill in the acquisition and use of knowledge. it is further argued that it is motivational and promotes critical thinking. Those institutiona who adopted this strategy were reviewed but some reverted to the classical form of teaching after giving it a try for some time. This Iloilo Doctor's College of Medicine its teaching curriculum using a correlated lecture series with a modified problem based orientation. After one year of implementation, its first year medical students wee given questionnaires to evaluate such teaching strategy. Independent variables used were the modified correlated lecture series manaement style, the instructional skills, classroom management and student faculty relations. Dependent variables include the academic excellence, average grade of the students, attendance, participation and development of student's leadership skills. Results are presented giving a favorable response to the program. Recommendations are worthwhile considering including the need to evaluate the new/younger members of the staff, the need to stress must know topics and better student faculty relationship.